Aberrant promoter hypermethylation regulates thrombomodulin in high altitude induced deep vein thrombosis. Issue 215 (July 2022) - Vijay, Aatira; Jha, Prabhash Kumar; Parveen, Seema; Goel, Shailendra; Prabhakar, Amit; Sharma, Swati; Kumar, Bhuvnesh; Chatterjee, Tathagata; Bajaj, Nitin; Nair, Velu; Sharma, Manish; Ashraf, Mohammad Zahid
Abstract: Background: DNA methylation regulates gene expression by inhibiting transcription factor binding to promoter and regulatory regions. Acute hypoxia during altitude exposure is associated with decreased natural anticoagulants and morbid thrombotic events. Thrombomodulin (TM) is a high affinity thrombin binding receptor protein, vital for vascular homeostasis. The purpose of this study is to determine gene expression regulation via methylation of TM gene in high altitude hypoxia induced deep vein thrombosis (DVT) patients. Materials and results: Percent 5-methyl cytosine analysis showed increased methylation in high altitude DVT patients (HAP) as compared to high altitude control (HAC) and seal level control (Control) subjects, while TM protein and mRNA levels were decreased in high altitude DVT patients as compared to other two groups. Bisulfite sequencing analysis indicated increased methylation in TM promoter in high altitude DVT patients compared to high altitude controls. Flow cytometry analysis showed decreased TM expression in hypoxia induced primary human umbilical vein endothelial cells (HUVECs). Treatment with specific DNA methyltransferase (DNMT) inhibitor-decitabine during hypoxia, restored TM expression. in vitro global methylation assay showed increased methylation in hypoxia group. Specific concentration of decitabine in hypoxia decreased global methylation showing a direct correlation between DNMTs and methylation. Selective dose of decitabine restored TM levels in HUVECs. DNMT1 and DNMT3B proteins showed to mediate the overall expression of TM. Conclusion: TM emerged as a potential candidate for methylation in high altitude DVT patients, regulated by hypoxia-induced epigenetic mechanism. Hypoxia culminates in methylation of DNA sequences in the promoter region of TM gene and increased the expression of DNMT1 and DNMT3B per se in primary HUVECs. Critical DNA methylation events were found to be compromised in high altitude DVT patients.